LOGISTICAL SUPPORT OF INDUSTRIAL ENTERPRISES: INNOVATIVE AND SAFETY COMPONENTS - DUMANSKA, Ilona (Herald of Khmelnytskyi National University. Economic sciences, 2025)
This article examines the relationship between innovation and security components that contribute to the competitive advantage of industrial logistics. Recognizing the importance of aligning advanced technologies with robust security protocols, the article aims to provide practical recommendations that industrial enterprises can apply to optimize their logistics structures. Key innovations such as digitalization, automation, data analytics, and modern transportation systems are analyzed, which demonstrate their important role in improving logistics operations and overall efficiency. A structural framework for identifying innovation components in new technologies and parameters for the methodological integration of innovation components in industrial logistics are substantiated. Among other things, the article includes a review of existing security protocols within this logistics framework, illustrating how the integration of innovative practices can ensure the protection of personnel, equipment, and the environment. Additionally, the article examines the combined impact of these innovative logistics support and security measures on performance indicators such as productivity, profitability, and security compliance. Assessing current logistics strategies, the research highlights how industrial enterprises can use innovative technologies to improve supply chain efficiency and responsiveness. The study identifies the following as best practices for combining innovation and security components: a culture of continuous improvement, regular assessment and acceptance of feedback, implementation of advanced technologies, compliance with regulatory requirements and industry standards, making informed decisions based on relevant data, collaboration between stakeholders, interaction and transparency in work, and training and development of personnel.